Interaction of Mutations Affecting Growth Rate and Resistance to Streptomycin in Pneumococci and Streptococci - Krauss, Marjorie R. (1966)
Krauss, Marjorie R. (New York University Medical Center, New York, N.Y.), James C. King, and Rody P. Cox. Interaction of mutations affecting growth rate and resistance to streptomycin in pneumococci and streptococci. J. Bacteriol. 92:1337–1344. 1966.—A strain of Streptococcus (Viridans group) was shown by transformation reactions to be the carrier of two interacting mutations. One produced resistance to streptomycin and a slow rate of growth; the only effect of the second was an increase in growth rate when it was added by transformation to streptococcal strains that had already been transformed to bear the first. Similar modifying mutations were observed in strains of streptococci and pneumococci into which the first mutation had been introduced by transformation.